DAMPAK PARIWISATA TERHADAP FENOMENA SEKULARISASI DALAM SENI PERTUNJUKAN WAYANG KULIT BALI (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study is to understand the impact of tourism on the phenomenon of secularization in Balinese shadow puppet performances. Tendencies to make worldly and rational interpretations are often called secularization. Therefore secularization can be understood as a realistic way of thinking or a basis of social and rational considerations, still placing religion as a moral guidelines. When secularization is defined as liberation, it does not mean free from the will of God, but free from magical and superstitious life. Secularization is also a form of modernization which is an innovation in the past due to the development of science (Black, 1967). Analyzing the Balinese shadow puppet art performance with the concepts of secularization does not mean that want to place the Balinese shadow puppet art performance free from religious goals but want to place the art shadow puppet performance functionally by experiencing rational processes in accordance with the realities being faced by society Bali. Creativity in the arts is not only directed on religious goals, but appears more as commercial creativity. As commercial creativity does not mean that religious creativity is lost. Shadow puppet performance art experiences a phenomenon of secularization, in this paper, it is not understood as a separation between the afterlife and worldly affairs, but is understood as a scientific process in science to become more scientific and argumentative.